The Effect of Balance Exercises on Success Level of Air Pistol Shooters - Ahmet Serhat Aydın; Serkan Revan (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to research the effects of air pistol balance shootings on shooting success, which performed for 12 weeks with certain air pistol shooters.